Comparative corrosion protection studies of electroactive/non-electroactive epoxy thermoset composites containing conductive rGO/non-conductive GO platelets - W. F. Ji; K. Y. Chen; C. J. Ke; Y. J. Liao; W. J. Liu; M. H. Tsai; J. M. Yeh (eXPRESS Polymer Letters)
In this study, comparative corrosion protection studies of cold-rolled steel (CRS) electrodes coated with electroactive/non-electroactive epoxy thermoset (denoted as EET/NEET) composites containing dispersed reduced graphene oxide (rGO) and graphene oxide (GO) platelets are presented. All composites were obtained through the thermal ring-opening reaction of bisphenol A diglycidyl ether (DGEBA) with amino-capped aniline trimer (ACAT) or trimethylolpropane tris[poly(propylene glycol), amine terminated] ether (T-403) at a specific mixing ratio in the presence of dispersed rGO/GO were characterized Fourier Transform Infrared (FTIR) spectroscopy and Transmission Electron Microscopy (TEM). In gas permeability measurements, the GO was found to display a slightly better dispersion capability in both EET and NEET membrane than in rGO. Conductive rGO platelets were found to promote the redox behavior of EET and non-conductive GO platelets was found to depress the redox behavior of EET, as measured by electrochemical cyclic voltammetry (CV) studies. Corrosion protection of composite coatings was investigated by electrochemical corrosion measurements in saline solution. It should be noted, in the EET system, that rGO was found to exhibit better anticorrosion performance as compared to that of GO. However, in NEET system, GO was found to have better anticorrosion performance than rGO. Better anticorrosion of rGO in EET may be attributed to better synergistic effect of electro-catalytic and the oxygen barrier properties of rGO in EET. On the contrary, better anticorrosion of GO in NEET may be associated with better oxygen barrier property of GO alone in NEET than that of rGO. The passive metal oxide layer formed on the cold rolled steel (CRS) electrode induced by EET was further confirmed by Raman and Electron Spectroscopy for Chemical Analysis (ESCA).